2011
DOI: 10.2478/s11536-011-0031-3
|View full text |Cite
|
Sign up to set email alerts
|

Is anemia at admission related to short-term outcomes of elderly hip fracture patients?

Abstract: AbstractHip fracture in elderly people is associated with high morbidity and mortality. Therefore, it is important to identify risk factors that potentially influence outcomes after hip surgery. The main purpose of this study was to evaluate the relationship of anemia at admission and short-term outcomes after hip fracture. We studied 343 community-dwelling patients who underwent surgery for hip fracture from March 2009 to March 2010. Functional mobility at discharge, postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Anaemia on admission was associated with increased mortality [17,18,20,22,25,27,28,33,36,40] at all time points beyond 30 days (Fig. 3), whether the anaemia was mild (Fig.…”
Section: Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…Anaemia on admission was associated with increased mortality [17,18,20,22,25,27,28,33,36,40] at all time points beyond 30 days (Fig. 3), whether the anaemia was mild (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…Four other studies reported statistically significant associations between pre-operative anaemia and mortality that we could not include in the meta-analysis [16,30,34,37]. The data for hospital length of stay, reported by seven studies, were unsuitable for meta-analysis [19,20,22,27,29,40,41]. Six studies found no association between admission anaemia and length of stay [19,20,22,29,40,41] and one reported that anaemia was associated with increased stays [27].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations